2012
DOI: 10.3109/03639045.2012.694890
|View full text |Cite
|
Sign up to set email alerts
|

Spray coating as a powerful technique in preparation of solid dispersions with enhanced desloratadine dissolution rate

Abstract: Solid dispersion systems have been widely used to enhance dissolution rate and oral bioavailability of poorly water-soluble drugs. However, the formulation process development and scale-up present a number of difficulties which has greatly limited their commercial applications. In this study, solid dispersions (SDs) of desloratadine (DSL) with povidone (PVP) and crospovidone (cPVP) were prepared by spray coating technique. The process involved the spray application of 96% ethanol solution of DSL and PVP/cPVP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The temperatures ranged from 2°C to 60°C and the relative humidity varied between 0% and 100%. The duration also varied significantly, with stability studies lasting from 24 h to two years (73,74,81,82,84,86,88,92,93,104,105,109,110,113,115,116,118,120,123,124,126,127,129,130,132,134,135,139,143,146,149,153,158,166,169,172,175,176). While most of the studies did not mention the container used for the physical stability test, a few specified, for example, whether a closed or open container was used (88,92,113,123,132,146).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…The temperatures ranged from 2°C to 60°C and the relative humidity varied between 0% and 100%. The duration also varied significantly, with stability studies lasting from 24 h to two years (73,74,81,82,84,86,88,92,93,104,105,109,110,113,115,116,118,120,123,124,126,127,129,130,132,134,135,139,143,146,149,153,158,166,169,172,175,176). While most of the studies did not mention the container used for the physical stability test, a few specified, for example, whether a closed or open container was used (88,92,113,123,132,146).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…Previous studies to improve the solubility of DES include the formation of complex inclusion of DES with β-cyclodextrin in a solution [ 31 ], and DES made in the form of hemifumarate salts to increase solubility [ 32 ]. A solid dispersion study of DES with povidone and crospovidone showed that it could increase the rate of drug dissolution [ 33 ]. Another study to increase the dissolution rate of DES with solid dispersion using poloxamer obtained results in amorphous form, which play a role in increasing intrinsic solubility [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of amorphous systems during spray coating is actually one of the most common applications of using the fluidised bed to improve physicochemical properties of poorly soluble drugs [42]. However, this is a key challenge that has to be overcome in the production of cocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…Fluidised bed spray coating has been successfully employed in the formation of drug-coated beads with enhanced dissolution properties and oral bioavailability [12]. One example is Sporanox ® which consists of an amorphous solid dispersion of itraconazole and hypromellose coated on sugar spheres [13].…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%